RESEARCH AND ANALYSIS OF PROBLEMS AND CHALLENGES IN ENSURING CYBERSECURITY IN CLOUD COMPUTING - Korol , Marta; Opirskyy, Ivan (Ukrainian Information Security Research Journal, 2024)
Cloud services provide information tools in a virtual environment with the ability to expand the software and hardware resources of a user’s computer device. In this case, the information is permanently stored on servers on the Internet and temporarily cached on client devices, such as personal computers, game consoles, laptops, smartphones, etc. To get constant access to remote Internet resources, users use cloud services. They are a key element of modern and rapidly developing technologies, and for many companies, the use of cloud services is a strategic issue. Although the innovative capabilities of cloud services attract the attention of users on the one hand, they can also pose new threats to their information security. That is why the study of cloud computing is important to understand its potential and effectiveness. This study will examine the security aspect of cloud services and compare several different platforms in this context, as the lack of sufficient protection can lead to theft of personal data and other confidential information. The study will also look at the most common threats faced by cloud services, such as DDoS attacks, data leaks, data misuse, etc. In particular, we will analyze the security measures provided by leading cloud platforms such as AWS, GCP and Azure to determine their effectiveness and reliability. Our analysis will be useful both for companies considering moving to the cloud and for ordinary users seeking to keep their personal data safe online. The results of the study will provide a clear picture of the benefits and limitations of using different cloud platforms from a security perspective.